2020
DOI: 10.1177/2167479520927993
|View full text |Cite
|
Sign up to set email alerts
|

Media Representations as a Form of Stacking: Male and Female Athletes Featured on Men’s Magazine Covers, 1980–2019

Abstract: This study analyzed 264 athlete images featured on the covers of nine men’s magazines across a 40-year period, 1980–2019. Among males, who accounted for 227 (81%) of the 264 athletes, African Americans and Latinos each represented 6 sports, most of which involved team competition, while White males represented 21 sports, many of which were individual. Analyses of position stacking in football showed White players in positions considered “central” to contest outcomes and Black athletes assigned to more “periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 72 publications
(80 reference statements)
2
9
0
Order By: Relevance
“…In contrast, the wide ranging and complex representations granted to non-racialized individuals allows them to see themselves as unique, important, and integral to an orderly society, reinforcing a positive sense of self (Mastro et al, 2011). For racialized individuals, however, their limited representation inhibits them from developing complex and positive understandings of their cultural and racial groups, which in turn can inhibit the development of multifaceted identities (Colburn & Melander, 2018; Denham, 2020; Mastro et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the wide ranging and complex representations granted to non-racialized individuals allows them to see themselves as unique, important, and integral to an orderly society, reinforcing a positive sense of self (Mastro et al, 2011). For racialized individuals, however, their limited representation inhibits them from developing complex and positive understandings of their cultural and racial groups, which in turn can inhibit the development of multifaceted identities (Colburn & Melander, 2018; Denham, 2020; Mastro et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These factors are at play in sports media. Recent studies have revealed that racialized individuals are rarely represented on the covers of sports magazines (Denham, 2020; Eagleman, 2011; Lawrence, 2016; Primm et al, 2007). Lawrence (2016) found that South Asian and Black men were the least represented in the UK edition of Men’s Health magazine from January/February 2010 to January/February 2011.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations